(untitled) (Baghdad Science Journal, 2004)
Design and Construction system for recording Finger print by laser, and separted the signal to noise by holographic element, was done. For safety, total reflection lighting ensures hat aser earns an not enter An operators eyes. Holographic diffraction grating was used instead of computer program to contrast images.